Associação de técnicas compensatórias ao sistema de drenagem urbana - Vielmo, Verônica Locatelli (2021)
With the growing of urbanization and the recurrence of flood events in the urban environment, it is shown that is necessary more knowledge about rainwater management. Then, the compensatory techniques presented are fundamental to improve the quality of overland flow and minimize your quantity; and so, soften the effects of superficial impermeabilization. This project presents the study of compensatory techniques association to the urban drainage system; capturing rainwater for enable the reuse in non-potable applications and decrease the peak flow, working together with the infiltration well, which favors the infiltration of excess accumulated flow through the capture system. It begins by characterizing the compensatory techniques and their applications and defining the most realizable system to a single family building. The project in question is focused in divide the responsibility between the public and private spheres about the rainwater flow demand. After, was calculated two suggestion of systems, with the infiltration well associated to the reservoir and apply of isolated form, assuming the inputs costs for implementation of the system. Finally, with the results obtained, it is possible to certify the efficiency of projected systems and measure theirs costs.